PSYCHOLOGICAL AND PEDAGOGICAL MECHANISMS OF INTEGRATING CHILDREN WITH SPECIAL NEEDS INTO THE GENERAL EDUCATION SYSTEM - Safieva Mokhinur Akramkizi (Bright Mind Publishing, 2025)
This article examines the psychological and pedagogical mechanisms that support the integration of children with special needs into the general education system. The study emphasizes the importance of inclusive education as a fundamental principle of modern pedagogy, aimed at ensuring equal opportunities and access to quality learning for all children. Psychological mechanisms are explored through the analysis of individual differences, motivation, emotional adaptation, and socialization processes, which directly affect the success of integration. Pedagogical mechanisms are considered through the design of adaptive teaching strategies, differentiated instruction, teacher professional competence, and collaboration with families and specialists. The article also highlights the challenges educators face in the process of integration, including the need for resource support, training in inclusive practices, and development of a tolerant educational environment. Practical implications include recommendations for improving psychological support services, establishing multidisciplinary teams, and creating flexible learning environments that promote the participation and well-being of children with special needs. The study concludes that successful integration requires a holistic approach that combines psychological understanding with pedagogical innovation, ultimately fostering not only academic progress but also social inclusion and personal development.
Keywords: Inclusive education, special needs, psychological mechanisms, pedagogical mechanisms, integration, socialization, differentiated instruction, adaptation, teacher competence, emotional development.